Factors Affecting the Desire to Become an Entrepreneur of Students in the Faculty of Business Administration, Savannakhet University - VONGKHASEUM, Bounphan; TOUNMANYSONE, Thongsa; MANIVONG, Khamkeo (Souphanouvong University Journal Multidisciplinary Research and Development, 2026)
The purpose of this study was to investigate the level of entrepreneurial intention among students at the Faculty of Business Administration, Savannakhet University, and to examine the factors influencing their desire to become entrepreneurs. The sample consisted of 414 respondents. Data were collected using a structured questionnaire and analyzed using quantitative methods, including descriptive statistics (mean and standard deviation) and probit regression analysis. The findings revealed a high level of entrepreneurial intention among students, particularly in terms of entrepreneurial attitudes, with a mean score of 3.87 and a standard deviation of 0.61. The factors significantly affecting students’ desire to become entrepreneurs were age, year of study, place of residence, and perceived behavioral control. The results of this study provide valuable insights for the development of policies and strategies aimed at more effectively promoting entrepreneurship among students.